Congenital Hyperinsulinism: Diagnosis and Treatment Update - Demirbilek, Hüseyin (J Clin Res Pediatr Endocrinol, 2017)
Pancreatic β-cells are finely tuned to secrete insulin so that plasma glucose levels are maintained within a narrow physiological range (3.5-5.5 mmol/L). Hyperinsulinaemic hypoglycaemia (HH) is the inappropriate secretion of insulin in the presence of low plasma glucose levels and leads to severe and persistent hypoglycaemia in neonates and children. Mutations in 12 different key genes (ABCC8, KCNJ11, GLUD1, GCK, HADH, SLC16A1, UCP2, HNF4A, HNF1A, HK1, PGM1 and PMM2) that are involved in the regulation of insulin secretion from pancreatic β-cells have been described to be responsible for the underlying molecular mechanisms leading to congenital HH. In HH due to the inhibitory effect of insulin on lipolysis and ketogenesis there is suppressed ketone body formation in the presence of hypoglycaemia thus leading to increased risk of hypoglycaemic brain injury. Therefore, a prompt diagnosis and immediate management of HH is essential to avoid hypoglycaemic brain injury and long-term neurological complications in children. Advances in molecular genetics, imaging techniques ((18)F-DOPA positron emission tomography/computed tomography scanning), medical therapy and surgical advances (laparoscopic and open pancreatectomy) have changed the management and improved the outcome of patients with HH. This review article provides an overview to the background, clinical presentation, diagnosis, molecular genetics and therapy in children with different forms of HH.